Withdrawal of Continuous Positive Airway Pressure Therapy after Malar Advancement and Le Fort II Distraction in a Case of Apert Syndrome with Obstructive Sleep Apnea. (14th September 2015) - Onda, Nobuto; Chiba, Shintaro; Moriwaki, Hiroto; Sawai, Rika; Yoshigoe, Akira; Watanabe, Subaru; Ando, Yuji; Uchida, Ryo; Miyawaki, Takeshi; Wada, Kota
Abstract : Apert syndrome is a congenital syndrome characterized by craniosynostosis and craniofacial dysostosis, among other features, and is reported to cause obstructive sleep apnea (OSA) because of upper airway narrowing associated with midfacial dysplasia. We recently encountered a case involving a patient with Apert syndrome complicated by OSA who began to receive continuous positive airway pressure (CPAP) therapy at the age of 4. OSA resolved after maxillofacial surgery performed at the age of 11, and CPAP was eventually withdrawn. In pediatric patients with maxillofacial dysplasia complicated by OSA, a long-term treatment plan including CPAP in addition to maxillofacial plastic and reconstructive surgery should be considered in view of the effects of OSA on growth.